L'érosion graduelle de la règle de l'étanchéité : une nouvelle menace à l'autonomie du Québec - Patenaude, Pierre (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
The exclusivity rule, an essential ingredient of provincial autonomy, has been weakened by recent Supreme Court decisions such as Coughlin v. Ontario Highway Transport Board, R. v. Smith, Re Anti-Inflation Act, Re Farm Products Marketing Act, and Caloil v. A.G. of Canada. Such an evolution can be dangerous for the people of Quebec because it might permit an invasion by the federal Parliament of Quebec's fields of exclusive jurisdiction. Until a new political agreement has been reached between Canada and Quebec, our Supreme Court should scrupulously adhere to the « watertight compartment » rule.